Social Support or Organizational Support: Which One Is More Predictive of Job Burnout in workers? - Farokhlegha Servat; Seyed Saeed Mazloomy Mahmoodabad; Masoumeh Abbasi- Shavazi; Ali Dehghani (Shahid Sadoughi University of Medical Sciences, 2020)
Introduction: Social and organizational supports are effective factors closely related to job burnout and Due to the limited studies in this area on Iranian workers, this study aims to determine the predictability of social support and organizational support in  job burnout for workers in Yazd. Methods: This cross-sectional study was carried out among 200 textile workers in Yazd through stratified random sampling. The data were collected by the tools including demographic characteristics, questionnaires of social support, organizational support, and Maslachchr('39')s job burnout. The data were analyzed by SPSS using the Pearson correlation coefficient and the multiple linear regressions. The Significance level of tests was considered as p <0.05.  Results: There was a significant strong positive relationship between job burnout and emotional exhaustion (r= 0.88) (p <0.001 (. There was found a significant negative correlation between job burnout and social support (r =- 0.390), friend support (r= -0.401), family supoert (r= -0.218), important others support (r= - 0.283) (p <0.001 (. Multiple linear regression analysis showed that 17.8% of the changes in job burnout were explained by friends, family, and important others support (R2=0.178, p<0.001) whereas support from friends was the strongest predictor of job burnout (β= - 0.338, p <0.001). Social and organizational support explained 35.9% of the changes in job burnout (R2= 0.359, p<0.001) with organizational support being the strongest predictor of  job burnout (β= - 0.472, p<0.001). Conclusion: Given that organizational support was the most significant predictor of job burnout in workers, developing organizational interventions to increase support in workplace can be regarded as effective strategy to reduce or slow down job burnout among workers.